A complete digital approach for facially generated full arch diagnostic wax up, guided surgery, and implant‐supported interim prosthesis by integrating 3D facial scanning, intraoral scan and CBCT. Issue 1 (19th October 2022) - Amin, Sara A.; Hann, Sean; Elsheikh, Ahmad Khater; Boltchi, Farhad; Zandinejad, Amirali
Abstract: Continuous innovation in digital dental technology offers new prospects for creating a complete virtual environment. The technique described adds a facial approach to the conventional digital workflow by incorporating 3D face scans to cone beam computed tomography and intraoral scans. Using this workflow, clinicians can obtain a complete virtual patient for facially generated diagnostic wax up and plan and implement a predictable implant placement and interim prosthesis. This technique provides a full digital workflow for restoratively‐driven computer‐aided implant planning, guided surgery, and 3D printing of an interim complete‐arch fixed implant‐supported prosthesis.